KEPASTIAN HUKUM AKTA PEMBERIAN HAK TANGGUNGAN TANPA SEPENGETAHUAN KURATOR ATAS HARTA DEBITOR PAILIT DAN AKIBAT HUKUMNYA - Zulkarnain, Debi; Maryano, Maryano; Mustafa, Marni Emmy (SENTRI: Jurnal Riset Ilmiah, 2024)
Bankruptcy is a general seizure of all the assets of a bankrupt debtor whose management and settlement is carried out by the curator under the supervision of the Supervising Judge. The debtor by law loses his right to control and take care of his property included in the bankruptcy estate from the date of the decision on the declaration of bankruptcy. The phenomenon that occurs is the transfer of the bankrupt debtor's property to another party after the bankruptcy decision is pronounced by The Commercial Court without the knowledge of the curator by making a deed of granting mortgage rights to the bankrupt debtor's property. The theory used in this writing is the theory of legal consequences according to Soeroso and the theory of legal certainty according to Jan Michiel Otto. The method used in this study with the type of normative research is legal research with secondary data using primary, secondary and tertiary sources of legal materials. The research approach used is the approach of legislation, conceptual, case, and analytical and legal material collection techniques carried out by identifying and inventorying positive legal rules, researching library materials and other sources of legal materials relevant to the legal issues under study. Legal material analysis technique is done by legal interpretation (interpretation) grammatical, historical and systematic. From the results obtained that the legal consequences of the deed of granting the mortgage without the knowledge of the curator of the bankrupt debtor's property is the deed of granting the mortgage is null and void, with the decision of the judge whose status has permanent legal force which gives sanctions in the form of cancellation of the deed of granting the mortgage, is a manifestation of the legal consequences. As for the legal certainty of the deed of granting a mortgage without the knowledge of the curator of the bankrupt debtor's property does not have legal certainty, with the judge's decision whose status has permanent legal force which states that the deed of granting the mortgage is null and void, the legal certainty of the deed of granting the mortgage has been realized.